The outputs of the angles of power output according to the method of (gaint set) and its effect on some biomechanical and physical indicators of the fifth barrier in the running of 110 m / hurdles of a category less than 20 - Naeem Ajeel, Ali; Basim Mohammed, Ali; Abdul Karim Al- Fadhli, Sareeh (International Journal of Psychosocial Rehabilitation, 2020)
The 110-meter hurdles race is one of the races that have achieved scientific progress at the level of training as well as at the level of selection, and this is what we noticed in the last Olympic Games as well as the World Championship, as there was a great competition for the first places, and this indicates the overlapping of various sciences in the training process aimed at refining mechanical performance to sync with physical abilities and these sciences , which have an advantage in this event Al mBiomechanics with two parts of kinematics and kinematics for the relatively short race distance compared to the fast and accurate physical performance of the race stages, and this made the research important to study the minutes and details of performance. The research problem was identified and built through continuous observation of the prior performance of the daily search sample exercises through the observed slow speed of crossing the barrier and the consequent movement performance over the barrier and the distance of the barrier and this slowness led to the emergence of some errors in the sense of the distance between the barriers in terms of the length and frequency of the step As the entirety of this case will inevitably lead to the renewal of these technical errors and their multiplication in the subsequent stages of the race as a result of a state of physical fatigue, this field problem prompted the researchers to study it and work on developing suggested and accurate training solutions to overcome it, and the researchers also used the experimental method to design the one group with the test. Tribal and postal, the research community consisted of 110 m runners hurdlers from the Sports Giftedness Center in Baghdad under 20 years old and their number is 4 runners if the research sample represented the community by 100%, and the researchers used training according to the method set The purpose of the research sample is to shed power outputs on muscle groups operating at several angles, resulting in an improvement in the mechanical performance of runners.